LEGAL ADJUDICATION, MATERIAL CORECCTNESS, AND MORAL OBJECTIVITY - Jorge L. Rodríguez (Eudaimonia)
The paper explores Wróblewski’s classical distinction between internal and external justification, highlighting two interpretations. According to the first, a decision is internally justified if it follows from the chosen premises and externally justified if those premises are also justified. From this perspective, some theorists have claimed that internal justification suffices for easy cases, while hard cases require external justification. However, it will be shown that this is a mistake arising from an ambiguity in the term “justification”, and clarifying this ambiguity reveals that both easy and hard cases require the same kind of justification. In the second interpretation, a decision is internally justified if it is derived from existing law and externally justified if its content is morally acceptable. This leads to an examination of the relationship between legal and moral justification. In this regard, Carlos Nino's claim that legal reasoning is a form of moral reasoning will be critically assessed by showing that it ultimately conflates the nature of norms with the nature of the reasons for their acceptance. Finally, it will be argued that moral objectivism is irrelevant for strong justification of judicial decisions (which requires valid reasoning with correct premises). Metaethical scepticism does not undermine substantive moral judgments or weaken moral debate, just as metaethical objectivism does not strengthen them.